Advances of Squamata astroglia to other reptiles : numerous astrocytes and glial fibrillary acidic protein (GFAP)-free areas : a preliminary study - Lőrincz, Dávid E.; Kálmán, Mihály (Acta Biologica Szegediensis, 2015)
Squamata are diapsid reptiles. Testudines were positioned formerly to the most ancient group, Anapsida, but recently they are also classified as diapsid reptiles, although their position within this group is uncertain. The investigated species of this study involved lizards (Timon tanginatus, Lacertidae; Pogona vitticeps, Agamidae; Eublepharis macularis, Gekkota; Chameleo calypratus, Chameleonidae), snakes (Epicrates cenchria maurus, Boidae; Python regius, Pythonidae; Pantherophis guttata and P. obsoletus quadrivittatus, Colubridae), and turtles (Testudo hermanni, Testudinidae; Trachemys scripta and Mauremyssinensis, Emydidae; Pelomedusa subrufa, Pleurodira). They were overanasthetised with Nembutal and transcardially perfused with 4% buffered paraformaldehyde. Coronal sections were processed according to the immunoperoxidase protocol. Monoclonal anti-GFAP and other glial markers were used. The main astroglia were the radial ependymoglia. There were two principal advances in Squamata. First, astrocytes were frequent in several areas, although, nowhere predominated. Furthermore, considerable GFAP-poor areas were found. They were extended in Python, and in Pogona and Chamaeleo GFAP was almost missing throughout the brain. The Squamata share more common astroglial features with birds than the turtles, although, represents a separate branch (Lepidosauria versus Archosauria). In mammals and birds the GFAP-free areas are usually advanced, expanded and plastic ones. Note that Squamata display quite complex behavioural phenomena related to other reptiles.